Aureobasidium pini sp. nov. from pine needle in China - Jiang, Ning; Liang, Ying-Mei; Tian, Cheng-Ming (Phytotaxa, 2019)
Aureobasidium is a yeast-like genus occurring on various substrates as pathogens, saprophytes or endophytes. In this study, Aureobasidium strains were isolated from needles of Pinus tabuliformis in China. The morphology and phylogeny evidences showed that it can be recognized as a new species. Hereby, Aureobasidium pini sp. nov. is introduced and it can be distinguished from its phylogenetically close species, A. namibiae by having shorter conidia.